Impact of growth promoting Bacillus subtilis on the growth and physiological characteristies of Date palm plantlets (Phoenix dactylifera L.) under salt stress. - Jassim, Naji Salim; Alhamd, Abdulrahman D (Journal of Kerbala for Agricultural Sciences, 2018)
The present study has been conducted at the lab. And green house of date palm research central Basrah University to evaluate the efficiency of Bacillus subtilis in date palm plantlets growth promoting, as well as, their effect on salt stress tolerance for treated date palm plants; during the season of 2016-2017. Results of lab. Experiments revealed the ability of B.subtilis to grow on various salt concentrations ,the colony forming units were 0.55, 0.44 and 0.43×108 cfu/ml of examined conc. Of 5, 10 and 15 ds.m-1 respectively . Green house experiment showed the efficiency of B.subtilis in date palm plant growth promoting undergo the treatments with a bove-mentioned salt concentrations, plant height ; fresh and dry weight of both root and shoot systems were increased significantly , additionally-significant increase of chlorophyll (a+b) contents were observed in B.subtilis treatment, compared with salt treatment only.